Temperature variability and hospitalization for cardiac arrhythmia in Brazil: A nationwide case-crossover study during 2000–2015 - Zhao, Q.; Coelho, M.; Li, S.; Saldiva, P.; Hu, K.; Abramson, M.; Huxley, Rachel; Guo, Y. (Elsevier Science Ltd, 2019)
© 2018 Elsevier Ltd Background: There is growing recognition of a potential role for environmental and climatic factors in influencing cardiovascular risk. It has been speculated that temperature variability (TV) is a risk factor for cardiac arrhythmia but evidence is limited. Objective: To quantify the geographic and demographic variations in the association between TV and hospitalization for cardiac arrhythmia in Brazil during 2000–2015. Methods: Data on hospitalization for arrhythmia and weather conditions were collected from 1,814 cities. TV was calculated as the standard deviation of daily maximum and minimum temperatures during exposure days. A time-stratified case-crossover approach was applied to examine the city-specific association between TV and hospitalization for arrhythmia. City-specific estimates were pooled at the national and regional levels using a random-effect meta-analysis. Stratified analyses were conducted by sex, three age-groups (0–64, 65–74 and =75 years), and three arrhythmia subtypes (paroxysmal tachycardia, atrial fibrillation and flutter, and other arrhythmias). Results: There were 447,667 arrhythmia-related hospitalizations during 2000–2015. The odds ratio of hospitalization per 1 °C increase in TV peaked on 0–1 days’ exposure [1.012 (95% confidence interval: 1.010–1.015)]. There were no substantial differences in effect estimates of TV0-1 by region, age or sex, except for the non-significant association observed in the north. However, women were more affected by prolonged TV exposure than men. For the three arrhythmias subtypes, only paroxysmal tachycardia and other arrhythmias were sensitive to TV. Assuming a causal relationship, 35,813 (95%CI: 18,302-51,665) cases were attributable to TV0-1 in Brazil during 2000–2015, accounting for 8.0% (95%CI: 4.1–11.5%) of hospitalizations for cardiac arrhythmia. Conclusions: At a population-level exposure to TV was associated with increased risk of arrhythmia-related hospitalization in Brazil, with the relationship equally distributed across most residents but varied by arrhythmia subtypes. Our findings add to the accumulating evidence-base that climatic factors can influence cardiovascular outcomes in populations.